Awareness of Self Breast Examination Among Medical Students of Peshawar, Khyber Pakhtunkhwa - Gandapur, Shireen Khan; Sardar, Aiman; Shah, Ameera Zahin; Khattak, Sana; Fazal, Sara; Munir, Hamza (Indus Journal of Bioscience Research, 2025)
The worldwide spread of breast cancer persists as the leading female cancer type while Pakistan faces rising challenges due to delayed detection and poor health education about the disease in the population. The self-breast examination (SBE) method provides an easy and economical approach to detect breast cancer early but medical students who will become healthcare professionals show limited adoption of this procedure. Research will evaluate SBE perceptions and familiarity along with understanding levels within medical students enrolled in Peshawar medical establishments of Khyber Pakhtunkhwa province. A survey with 600 MBBS students was distributed across six medical colleges which included three public institutions and three private ones. The study showed that numerous students possessed some understanding of SBE yet there were substantial gaps between education and practical applications. Multiple barriers including cultural differences culture-related obstacles and social prejudice served to block SBE promotion efforts. The research shows that medical education and public health strategies should use enhanced curricula to cultivate medical students into breast cancer awareness advocates for regions which suffer from limited medical resources. These results create essential knowledge for designing interventions which will enhance breast health awareness and detection practices among future Pakistani healthcare professionals.